Bimetal MOFs-loaded electrostatic spinning fiber membrane for oil-water separation and preparation method of bimetal MOFs-loaded electrostatic spinning fiber membrane
By growing bimetallic MOFs on the surface of electrospun fiber membranes, the problem of poor separation effect in existing oil-water separation technologies is solved, and efficient degradation of organic pollutants under visible light and long-lived use of the membrane is achieved.
Patent Information
- Application Number
- CN202510583590.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-07
- Publication Date
- 2025-08-08
AI Technical Summary
The existing oil-water separation technology has high economic costs, a single separation membrane structure, poor separation effect on multiple mixtures, and poor recyclability, making it difficult to meet the needs of efficient separation in complex environments.
Bimetal MOFs were grown on the surface of the electrospun fiber membrane through electrospun technology, and electrospun fiber membranes loaded with bimetal MOFs were prepared by solvothermal method. The core-satellite structures of MIL-53(Fe) and MIL-53(Al)-OH were combined to enhance the adsorption and photocatalytic properties of the film.
High selectivity, high throughput oil-water separation is achieved, and excellent degradation ability to organic pollutants under visible light, extending the service life of the membrane.
Smart Images

Figure CN120437841A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of membrane separation, and in particular to an electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation and a preparation method thereof. Background Art
[0002] In the process of rapid urbanization and industrialization, the large-scale discharge of oily wastewater poses a severe challenge to the ecological environment, and its efficient treatment and resource utilization have gradually become the focus of social attention. Traditional oil-water separation technology has the disadvantages of high economic cost, single separation membrane structure, poor separation effect on multiple mixtures, poor recyclability, etc., which makes it difficult to meet the growing market separation needs. Compared with traditional oil-water separation membrane materials, nanofiber membranes prepared by electrospinning technology have the advantages of large specific surface area and strong designability, and have gradually become a popular material for oil-water separation membranes. For example, Chinese patent document No. CN116043416A discloses an electrospun super-hydrophobic membrane for oil-water separation. The invention immerses the nitrocellulose membrane prepared by electrospinning into an amino silicone oil solution for 20min-50min and then dries it, then immerses it in a gas phase particle solution for 20min-50min and then dries it at room temperature to obtain an electrospun super-hydrophobic membrane with high oil-water separation efficiency and is reusable. Chinese patent publication CN108579447A discloses a super-hydrophilic electrospun fiber membrane for oil-water separation. The invention first prepares a grafted polymer from polyvinylidene fluoride and other raw materials, then uses electrospinning technology to prepare an electrospun fiber membrane. Further heat treatment yields the super-hydrophilic electrospun fiber membrane for oil-water separation. However, an ideal liquid filtration material should possess high selectivity, high flux, high filtration efficiency, low filtration resistance, adsorption and degradation of organic pollutants, resistance to biofouling, and a long service life, and be suitable for use in a variety of complex environments.
[0003] Metal-organic frameworks (MOFs) are a class of porous crystalline materials formed by the self-assembly of metal ions or metal clusters with organic ligands through coordination bonds. Due to their large specific surface area, easily modifiable framework structure, and high designability, they are widely used in water treatment, gas separation, drug delivery, catalysis, and other fields. Combining MOFs with membrane materials to create synergistic, multifunctional composite membranes can not only effectively address nanoparticle recovery issues, but also improve membrane filtration performance, mechanical strength, and reusability.
[0004] Chinese patent document CN110496541A discloses a modified composite fiber membrane for oil-water separation and a preparation method thereof. The invention mixes a solution containing PAN with a solution containing MOFs to obtain a casting solution, and the casting solution is electrospinned to produce a base membrane; the base membrane is dried and coated with fluorosilane vapor to obtain a nanofiber membrane. The MOFs material is evenly distributed in the fibers, and the water contact angle of the membrane surface reaches superhydrophobic conditions. However, this method may cause the MOFs to be coated by the spinning solution, thereby affecting their adsorption or degradation efficiency. Summary of the Invention
[0005] In response to the above-mentioned shortcomings in the prior art, the present invention provides a method for preparing an electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation. Bimetallic MOFs are grown on the surface of the electrospun fiber through electrospinning technology and solvent thermal method. The obtained electrospun fiber membrane loaded with bimetallic MOFs has good oil-water separation performance, excellent anti-fouling ability and dye degradation ability.
[0006] The specific technical solutions adopted are as follows:
[0007] A method for preparing an electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation comprises the following steps:
[0008] (1) The hydroxyl-modified metal-organic framework material MIL-53(Al)-OH was prepared by solvothermal reaction;
[0009] (2) preparing a MIL-53(Fe) precursor solution using iron salt, terephthalic acid, polyvinyl pyrrolidone and an organic solvent, ultrasonically dispersing the MIL-53(Al)-OH prepared in step (1) therein, mixing well, and immersing the electrospun fiber membrane in the above solution system for 1-3 hours;
[0010] (3) The system of step (2) is further transferred to a reactor, and the reaction is carried out at 130-150° C. for 10-15 hours to allow the bimetallic MOFs to grow on the surface of the electrospun fiber membrane. After washing and drying, the electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation is obtained.
[0011] The present invention grows bimetallic MOFs on the surface of electrospun fibers through electrospinning technology and solvent thermal method. The electrospun fibers have a large specific surface area and good mechanical strength. After being loaded with bimetallic MOFs with strong adsorption and photocatalytic capabilities, the bimetallic MOFs can degrade organic pollutants adsorbed on the membrane under light, thereby effectively improving the characteristics of the fiber membrane that are easy to clog and pollute.
[0012] Polyvinylpyrrolidone (PVP) plays a key role in guiding the structure. MIL-53(Fe) has a high affinity with MIL-53(Al)-OH and PVP has a high affinity with Fe in MIL-53(Fe). 3+ The polar groups of MIL-53(Al)-OH interact with each other. The zeta potential of MIL-53(Al)-OH is +6.72 mV, while that of PVP is -0.27 mV. Due to electrostatic attraction, PVP forms several layers on the MIL-53(Al)-OH nanoparticles. As the reaction proceeds, MIL-53(Fe) expands and grows, forming a core-satellite hybrid structure with MIL-53(Al)-OH as satellites and MIL-53(Fe) as the core. Furthermore, the two MOFs share the same ligands but different metal centers. Under hydrothermal conditions at 150°C, MIL-53(Fe) rapidly and homogeneously nucleates, while MIL-53(Al)-OH heterogeneously nucleates on MIL-53(Fe), forming a MOF-on-MOF hybrid. Unlike core-shell structures, this structure does not completely encapsulate MIL-53(Fe), preserving the visible light contact area of MIL-53(Fe) without compromising catalytic efficiency.
[0013] Preferably, in step (1), the preparation method of MIL-53(Al)-OH is: preparing a MIL-53(Al)-OH precursor solution using aluminum salt, 2,5-dihydroxyterephthalic acid, terephthalic acid and an organic solvent, transferring the MIL-53(Al)-OH precursor solution to a reactor, reacting at 100-120°C for 6-10h, washing and drying to obtain MIL-53(Al)-OH.
[0014] More preferably, in the MIL-53(Al)-OH precursor solution, the concentration of aluminum salt is 0.3-0.5 mol / L, the concentration of 2,5-dihydroxyterephthalic acid is 0.05-0.15 mol / L, and the concentration of terephthalic acid is 0.05-0.15 mol / L.
[0015] Preferably, in step (2), in the MIL-53(Fe) precursor solution, the concentration of iron salt is 0.1-0.3 mol / L, the concentration of terephthalic acid is 0.05-0.15 mol / L, and the concentration of polyvinylpyrrolidone (average molecular weight 58,000) is 5-15 g / L.
[0016] Preferably, in step (2), the amount of MIL-53(Al)-OH added to the MIL-53(Fe) precursor solution ensures a molar ratio of Al in MIL-53(Al)-OH to Fe in the MIL-53(Fe) precursor solution of 1.5-2:1. The structure prepared using this ratio can ensure a core-satellite structure, and the aluminum-based MOF will not completely cover the iron-based MOF.
[0017] Optionally, the electrospun fiber membrane is a nylon PA66 electrospun fiber membrane, a polysulfone PSF electrospun fiber membrane or a polyvinyl pyrrolidone PVP-polytetrafluoroethylene PTFE electrospun fiber membrane.
[0018] The polymer spinning solution is made into an electrospun fiber membrane through electrospinning technology. Further preferably, the mass concentration of the polymer in the polymer spinning solution is 12 to 25 wt%; the parameters of the electrospinning process are: voltage of 12 to 20 kV, distance from the spinneret to the collector of 10 to 20 cm, flow rate of 0.2 to 1.0 mL / h, ambient temperature of 20 to 30 ° C, and ambient humidity of 40% to 50%.
[0019] The present invention also provides an electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation prepared by the preparation method of the electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation.
[0020] The present invention also provides an oil-water separation method using the electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The bimetallic MOFs nanoparticles (MIL-53(Al,Fe)-OH) prepared by using PVP as a structure-directing agent in the present invention have both the excellent photocatalytic performance of MIL-53(Fe) and the excellent adsorption performance of MIL-53(Al)-OH. Compared with monometallic MOFs, they exhibit good adsorption and photocatalytic performance under both dark light and visible light irradiation. MIL-53(Al,Fe)-OH has the highest removal rate for methylene blue (MB) (nearly 100%), while MIL-53(Fe) and MIL-53(Al)-OH have poor MB degradation efficiency, which is only about 65% and 40%, respectively, due to their poor adsorption and light absorption. In addition, the method of synthesizing bimetallic MOFs by adding pre-synthesized metal MOFs to the precursor solution of another MOF is more efficient than the method of synthesizing bimetallic MOFs using a bimetallic precursor mixture solution, and bimetallic MOFs with appropriate growth parameters exhibit the best MB adsorption-catalytic synergistic efficiency.
[0023] (2) In this paper, bimetallic MOFs nanoparticles (MIL-53(Al,Fe)-OH) are loaded on the surface of PA66 electrospun fiber membrane. The prepared PA66@MIL-53(Al,Fe)-OH membrane has high selective wettability, excellent antifouling properties and catalytic activity. The separation flux of the membrane for high viscosity soybean oil emulsion reaches 16805.87 L·m -2 ·h -1 The flux recovery rate (FRR) was 86.60%, and the degradation rate of MB under visible light irradiation reached 96%. The hydrophilic groups on the membrane surface and the rough structure synergistically formed a stable hydration layer, which effectively reduced the adhesion of oil droplets. At the same time, bimetallic MOFs can achieve efficient degradation of organic pollutants through adsorption-catalytic synergy. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 TEM images of bimetallic MOFs (MIL-53(Al,Fe)-OH) at different magnifications. The scale bars in a and b are 1 μm, and the scale bar in c is 200 nm.
[0025] Figure 2 The following are SEM images of different product films, where a is comparative example 1, b is comparative example 2, and c and d are SEM images of Example 1 at different magnifications.
[0026] Figure 3 Statistical diagram of water flux before and after separation of soybean oil emulsion by different product membranes (operating pressure is 0.1MPa).
[0027] Figure 4 Statistical diagram of the adsorption-photocatalytic degradation efficiency of methylene blue MB by different product membranes. DETAILED DESCRIPTION
[0028] In order to make the objects, features and advantages of the present invention more clearly understood, a detailed description is given below using specific embodiments. In the following description, many specific details are set forth to fully understand the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below. The technical features in the various embodiments of the present invention can be combined accordingly without conflicting with each other.
[0029] The operating methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or the conditions recommended by the manufacturer. The contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0030] Example 1
[0031] (1) Nylon PA66 formic acid solution was prepared into nylon PA66 electrospun fiber membrane by electrospinning technology. The mass concentration of nylon PA66 in the nylon PA66 formic acid solution was 15wt%. During the electrospinning process: the voltage was 20kV, the distance from the spinneret to the collector was 15cm, the flow rate of the nylon PA66 formic acid solution was 0.3mL / h, the spinning time was 6h, the ambient temperature was 20-30℃, and the ambient humidity was 40%-50%.
[0032] (2) The hydroxyl-modified metal-organic framework (MIL-53(Al)-OH) was prepared by a solvothermal reaction. 0.966 g (4 mmol) of AlCl3·6H2O, 0.199 g (1 mmol) of 2,5-dihydroxyterephthalic acid, and 0.166 g (1 mmol) of terephthalic acid were dissolved in 10 mL of N,N-dimethylformamide (DMF) to obtain a precursor solution. The precursor solution was transferred to a PTFE-lined autoclave and heated at 120°C for 8 h. The product was filtered and washed twice by centrifugation with MeOH and EtOH, respectively, and then dried and activated in an oven overnight. The resulting yellow product was MIL-53(Al)-OH.
[0033] (3) 0.541 g (2 mmol) of FeCl3·6H2O, 0.166 g (1 mmol) of terephthalic acid, and the prepared MIL-53(Al)-OH powder (0.15 g) were ultrasonically dispersed in 10 mL of DMF and 0.1 g of PVP (average molecular weight 58,000) was added and mixed, where PVP was used as a structure-directing agent.
[0034] (4) The PA66 electrospun fiber membrane was immersed in the precursor solution obtained in step (3) at room temperature for 2 hours, and then the above system was transferred to a reactor and reacted at a temperature of 150°C for 12 hours to allow the bimetallic MOFs to grow uniformly on the surface of the PA66 electrospun fiber membrane. After washing and drying, the bimetallic MOFs-loaded electrospun fiber membrane for oil-water separation (PA66@MIL-53(Al,Fe)-OH membrane) was obtained.
[0035] Example 2
[0036] (1) N,N-dimethylformamide (DMF) and acetone were mixed in a mass ratio of 9:1 as a mixed solvent for polysulfone, polysulfone was dissolved in the above mixed solvent to prepare a polysulfone solution with a mass fraction of 20 wt%, and the polysulfone solution was prepared into a polysulfone PSF electrospun fiber membrane by electrospinning technology. During the electrospinning process: the voltage was 12 kV, the distance from the spinneret to the collector was 20 cm, the flow rate of the polysulfone solution was 0.8 mL / h, the spinning time was 6 h, the ambient temperature was 20-30 ° C, and the ambient humidity was 40%-50%.
[0037] (2) The hydroxyl-modified metal-organic framework (MIL-53(Al)-OH) was prepared by a solvothermal reaction. 0.966 g (4 mmol) of AlCl3·6H2O, 0.199 g (1 mmol) of 2,5-dihydroxyterephthalic acid, and 0.166 g (1 mmol) of terephthalic acid were dissolved in 10 mL of N,N-dimethylformamide (DMF) to obtain a precursor solution. The precursor solution was transferred to a PTFE-lined autoclave and heated at 120°C for 8 h. The product was filtered and washed twice by centrifugation with MeOH and EtOH, respectively, and then dried and activated in an oven overnight. The resulting yellow product was MIL-53(Al)-OH.
[0038] (3) 0.541 g (2 mmol) of FeCl3·6H2O, 0.166 g (1 mmol) of terephthalic acid, and the prepared MIL-53(Al)-OH powder (0.15 g) were ultrasonically dispersed in 10 mL of DMF and 0.1 g of PVP (average molecular weight 58,000) was added and mixed evenly, where PVP was used as a structure-directing agent.
[0039] (4) The polysulfone PSF electrospun fiber membrane was immersed in the precursor solution prepared in step (3) at room temperature for 2 hours, and then the above system was transferred to a reactor and reacted at a temperature of 150°C for 12 hours to allow the bimetallic MOFs to grow uniformly on the surface of the polysulfone PSF electrospun fiber membrane. After washing and drying, the bimetallic MOFs-loaded electrospun fiber membrane for oil-water separation (PSF@MIL-53(Al,Fe)-OH membrane) was obtained.
[0040] Example 3
[0041] (1) PVP polymer powder was placed in a conical flask, anhydrous ethanol was added, and the mixture was stirred until completely dissolved to prepare a colorless and transparent PVP solution, and then polytetrafluoroethylene (PTFE) emulsion was added to obtain a PVP-PTFE spinning solution with a mass fraction of 24 wt%. The PVP-PTFE spinning solution was prepared into a PVP-PTFE electrospun fiber membrane by electrospinning technology. During the electrospinning process, the voltage was 15.5 kV, the distance from the spinneret to the collector was 19 cm, the flow rate of the PVP-PTFE spinning solution was 0.3 mL / h, the spinning time was 6 h, the ambient temperature was 20-30 ° C, and the ambient humidity was 40%-50%.
[0042] (2) The hydroxyl-modified metal-organic framework (MIL-53(Al)-OH) was prepared by a solvothermal reaction. 0.966 g (4 mmol) of AlCl3·6H2O, 0.199 g (1 mmol) of 2,5-dihydroxyterephthalic acid, and 0.166 g (1 mmol) of terephthalic acid were dissolved in 10 mL of N,N-dimethylformamide (DMF) to obtain a precursor solution. The precursor solution was transferred to a PTFE-lined autoclave and heated at 120°C for 8 h. The product was filtered and washed twice by centrifugation with MeOH and EtOH, respectively, and then dried and activated in an oven overnight. The resulting yellow product was MIL-53(Al)-OH.
[0043] (3) 0.541 g (2 mmol) of FeCl3·6H2O, 0.166 g (1 mmol) of terephthalic acid, and the prepared MIL-53(Al)-OH powder (0.15 g) were ultrasonically dispersed in 10 mL of DMF and 0.1 g of PVP (average molecular weight 58,000) was added and mixed evenly, where PVP was used as a structure-directing agent.
[0044] (4) The PVP-PTFE electrospun fiber membrane was immersed in the precursor solution prepared in step (3) at room temperature for 2 h, and then the above system was transferred to a reactor and reacted at a temperature of 150°C for 12 h to allow the bimetallic MOFs to grow uniformly on the surface of the PVP-PTFE electrospun fiber membrane. After washing and drying, the bimetallic MOFs-loaded electrospun fiber membrane for oil-water separation (PVP-PTFE@MIL-53(Al,Fe)-OH membrane) was obtained.
[0045] Comparative Example 1
[0046] Nylon PA66 formic acid solution was made into nylon PA66 electrospun fiber membrane by electrospinning technology. The mass concentration of nylon PA66 in the nylon PA66 formic acid solution was 15wt%. During the electrospinning process: the voltage was 20kV, the distance from the spinneret to the collector was 15cm, the flow rate of the nylon PA66 formic acid solution was 0.3mL / h, the spinning time was 6h, the ambient temperature was 20-30℃, and the ambient humidity was 40%-50%.
[0047] Comparative Example 2
[0048] 5.41 g of FeCl3·6H2O, 1.98 g of terephthalic acid, 100 mL of DMF and 1 g of PVP (average molecular weight 58,000) were added to a beaker and stirred thoroughly to prepare a MIL-53(Fe) precursor solution. After complete dissolution, the PA66 electrospun fiber membrane in Comparative Example 1 was immersed in the precursor solution at room temperature for 2 hours. The above system was then transferred together to a reactor and reacted at 150°C for 12 hours to allow MIL-53(Fe) to grow uniformly on the surface of the PA66 electrospun fiber membrane. Afterwards, the PA66@MIL-53(Fe) membrane was obtained after washing and drying.
[0049] Comparative Example 3
[0050] 0.966 g (4 mmol) of AlCl3·6H2O, 0.199 g (1 mmol) of 2,5-dihydroxyterephthalic acid and 0.166 g (1 mmol) of terephthalic acid were dissolved in 10 mL of DMF to obtain a MIL-53(Al)-OH precursor solution. After complete dissolution, the PA66 electrospun fiber membrane in Comparative Example 1 was immersed in the precursor solution at room temperature for 2 h. Then, the above system was transferred to a reactor and reacted at 110°C for 12 h to allow MIL-53(Al)-OH to grow uniformly on the surface of the PA66 electrospun fiber membrane. After washing and drying, the PA66@MIL-53(Al)-OH membrane was obtained.
[0051] Sample analysis
[0052] Figure 1 These are TEM images of bimetallic MOFs (MIL-53(Al,Fe)-OH) of different magnifications synthesized in the examples. The scale bars in a and b are 1 μm, and the scale bar in c is 200 nm. MIL-53(Al,Fe)-OH presents a core-satellite structure. The average particle size of MIL-53(Fe) is large and columnar; the average particle size of MIL-53(Al)-OH is small and irregularly dispersed on the surface of MIL-53(Fe), indicating that bimetallic MOFs with a core-satellite structure were successfully synthesized by the internal extension growth method, and MIL-53(Al)-OH formed a relatively uniform interface contact on the surface of MIL-53(Fe).
[0053] Figure 2 Figure 2 is the SEM image of different product films, where a is comparative example 1, b is comparative example 2, and c and d are SEM images of Example 1 at different magnifications. Figure 2 As can be seen from a in the figure, pure PA66 nanofibers are smooth. Figure 2 In b, it can be seen that MIL-53(Fe) grows on PA66 fibers in an irregular prism shape; Figure 2As can be seen in Figures c and d, part of the MIL-53(Al,Fe)-OH grows on the surface of the PA66 fiber, and some of the PA66 fibers also have MIL-53(Al)-OH nanoparticles growing on them. This is because some of the MIL-53(Al)-OH nanoparticles do not react with the MIL-53(Fe) precursor but are combined with the PA66 fiber through hydrogen bonds.
[0054] Using sodium lauryl sulfate (0.2g) as an emulsifier, 1mL of soybean oil was mixed with 999mL of water in a high-shear homogenizer for 0.5h. Optical microscope images showed that the droplet size of all the emulsions produced was less than 10μm and the emulsified state could be maintained for more than 24h. The water flux statistics of different membrane products before and after the separation of soybean oil emulsions are shown in Figure 2. Figure 3 As shown in the figure, it can be seen that the soybean oil emulsion flux of the membrane of Example 1 is 16805.87 L·m -2 ·h -1 , and the flux recovery rate can reach 86.60%; the soybean emulsion flux of the membrane in comparative example 1 is 10535.43 L·m -2 ·h -1 The flux recovery rate was 23.44%. The soybean emulsion flux of the membrane in comparative example 3 was 12147.06 L·m -2 ·h -1 The flux recovery rate is 98.83%. That is, the separation flux of the electrospun fiber membrane loaded with bimetallic MOFs of the present invention is better than that of Comparative Example 1 and Comparative Example 3.
[0055] The concentration is 10 mg·L -1 MB solution was added to a glass beaker. Then, 10 mg of the product membrane was accurately weighed and added to a glass beaker containing 50 mL of dye solution, and the beaker was placed in a dark environment for adsorption for 120 minutes to ensure that the bimetallic MOFs powder reached adsorption equilibrium. The glass beaker was then placed directly under a 300W xenon lamp for a photocatalytic dye degradation experiment. After each 30 minutes of illumination, the supernatant solution in the glass bottle was extracted using a syringe and placed in a UV spectrophotometer to measure the dye absorbance, and then the corresponding dye concentration was calculated based on the dye standard curve. The experiment ended after 120 minutes of illumination. The results are as follows. Figure 4 As shown, the MB degradation efficiency of the different samples is ranked from high to low as Example 1 > Comparative Example 2 > Comparative Example 1. Example 1 has the highest MB removal rate, reaching 95.85% after 2 hours of photocatalysis, while Comparative Example 2 has a MB degradation efficiency of 75.67%. This indicates that the bimetallic composite membrane of the present invention outperforms both Comparative Examples 1 and 2 in terms of dye degradation performance.
[0056] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing an electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation, characterized in that: The following steps are involved: (1) The hydroxyl-modified metal-organic framework material MIL-53(Al)-OH was prepared by solvothermal reaction; (2) preparing a MIL-53(Fe) precursor solution using iron salt, terephthalic acid, polyvinyl pyrrolidone and an organic solvent, ultrasonically dispersing the MIL-53(Al)-OH prepared in step (1) therein, mixing well, and immersing the electrospun fiber membrane in the above solution system for 1-3 hours; (3) The system of step (2) is further transferred to a reactor, and the reaction is carried out at 130-150° C. for 10-15 hours to allow the bimetallic MOFs to grow on the surface of the electrospun fiber membrane. After washing and drying, the electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation is obtained.
2. The method for preparing an electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation according to claim 1, characterized in that: In step (1), the preparation method of MIL-53(Al)-OH is: using aluminum salt, 2,5-dihydroxyterephthalic acid, terephthalic acid and organic solvent to prepare a MIL-53(Al)-OH precursor solution, transferring the MIL-53(Al)-OH precursor solution to a reactor, reacting at 100-120°C for 6-10h, washing and drying to obtain MIL-53(Al)-OH.
3. The method for preparing an electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation according to claim 2, characterized in that: In the MIL-53(Al)-OH precursor solution, the concentration of aluminum salt is 0.3-0.5 mol / L, the concentration of 2,5-dihydroxyterephthalic acid is 0.05-0.15 mol / L, and the concentration of terephthalic acid is 0.05-0.15 mol / L.
4. The method for preparing an electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation according to claim 1, characterized in that: In step (2), in the MIL-53(Fe) precursor solution, the concentration of iron salt is 0.1-0.3 mol / L, the concentration of terephthalic acid is 0.05-0.15 mol / L, and the concentration of polyvinylpyrrolidone is 5-15 g / L.
5. The method for preparing an electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation according to claim 1, characterized in that: In step (2), the amount of MIL-53(Al)-OH added to the MIL-53(Fe) precursor solution ensures that the molar ratio of Al element in MIL-53(Al)-OH to Fe element in the MIL-53(Fe) precursor solution is 1.5-2:
1.
6. The method for preparing an electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation according to claim 1, characterized in that: The electrospun fiber membrane is a nylon PA66 electrospun fiber membrane, a polysulfone PSF electrospun fiber membrane or a polyvinyl pyrrolidone PVP-polytetrafluoroethylene PTFE electrospun fiber membrane.
7. The method for preparing an electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation according to claim 1, characterized in that: The electrospinning process comprises the following steps: a polymer spinning solution is prepared into an electrospinning fiber membrane by electrospinning technology, wherein the mass concentration of the polymer in the polymer spinning solution is 12 to 25 wt %. The electrospinning process comprises the following parameters: a voltage of 12 to 20 kV, a distance from the spinneret to the collector of 10 to 20 cm, a flow rate of 0.2 to 1.0 mL / h, an ambient temperature of 20 to 30° C., and an ambient humidity of 40 to 50%.
8. An electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation prepared according to the method for preparing an electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation according to any one of claims 1 to 7.
9. An oil-water separation method, characterized in that: The electrospun fiber membrane loaded with bimetallic MOFs for oil-water separation according to claim 8 is used.
Citation Information
Patent Citations
Super-hydrophilic electrostatic spinning fiber membrane for oil and water separation and preparation method
CN108579447A
Modified composite fiber membrane for oil-water separation, and preparation method thereof
CN110496541A
Electrostatic spinning super-hydrophobic membrane for oil-water separation and preparation method thereof
CN116043416A
Cited By
Energy-saving and environment-friendly treatment method for spinning electrostatic deoiling sewage
CN121181110A
Energy-saving and environment-friendly treatment method for spinning electrostatic deoiling water
CN121181110B